Hydrogen photogeneration using ternary CuGaS2-TiO2-Pt nanocomposites. (13th January 2020) - Caudillo-Flores, Uriel; Kubacka, Anna; Berestok, Taisiia; Zhang, Ting; Llorca, Jordi; Arbiol, Jordi; Cabot, Andreu; Fernández-García, Marcos
Abstract: In this contribution we synthesized ternary CuGaS2 -TiO2 -Pt materials. The semiconductor components were surface functionalized with mercapto-alifatic acids to drive their linking and were platinized prior to or after contact between the semiconductors. The corresponding samples were utilized in the photo-production of hydrogen using methanol as a sacrificial agent. The testing under UV and visible illumination conditions together with the calculation of the true quantum efficiency of the process demonstrate the outstanding performance of these ternary materials under sunlight operation. Optimum activity was achieved for samples having a 3 to 5 wt % of the chalcogenide and a selective interaction of the noble metal with the major oxide component. The physico-chemical characterization and particularly the use of photoluminescence spectroscopy showed that photo-activity is controlled by charge separation under illumination, which drives to charge location of electrons and holes in different components of the powders and the efficient use of charge carriers in the chemical reaction. Highlights: CuGaS2 -TiO2 -Pt materials tested under UV and Visible light hydrogen photo-production. Analysis of activity by means of the true quantum efficiency. A 3–5 %wt CuGaS2 content optimizes activity under all illumination conditions tested. Activity is directly linked with charge rcombination.